Studies on the Activity and Composition of Soil Microbial Communities in Rescource Limited Soils. - English, Lorna Christina (University of Stirling, 2006)
Soils from two resource limited sites were sampled and various chemical and microbial parameters measured. The sites chosen were Signy Island in the maritime Antarctic and the southern slopes of Mt Etna in Sicily. The soil from the Antarctic was resource limited due to the severe nature of its habitat, very cold and windy. There were several soils analysed from Mt Etna from young developing soils to older more established soils. The soils from the Antarctic had low concentrations of carbon and nitrogen and with a carbon to nitrogen ratio of 10. Initial analyses showed that they had a low microbial diversity but after the addition of plant residues the diversity increased with time. The young soils from Mount Etna behaved in a similar way to the soils from Antarctica. They had low carbon and nitrogen levels and a low microbial biomass. When plant material was added to the soil they were able to decompose it readily. By contrast the older volcanic soils had higher levels of carbon and nitrogen and a more diverse microbial community.